Diagenetic history of the upper Tanglewood Member (upper Ordovician) of the Lexington Limestone, central Kentucky, U.S.A. with special emphasis on petrographic differences between deformed and undeformed beds (Journal of Nepal Geological Society, 2017)
Petrographic study was carried out for the upper Tanglewood Member (upper Ordovician) of the Lexington Limestone in order to understand its diagenetic history and predict whether the cementation is pre-deformational or post-deformational by comparing the deformed and undeformed beds of the same horizon. This study shows that the diagenetic processes, which have modified the sequence of the upper Tanglewood Member of the Lexington Limestone, consist of micritization, cementation, compaction, dolomitization and internal filling. Moreover, it indicates that the main episode of cementation took place after the sediment deformation.